How Does Human Capital Matter? Evidence from Venture Capital - Gu, Lifeng; Huang, Ruidi; Mao, Yifei; Tian, Xuan (Journal of Financial and Quantitative Analysis, 2022)
Abstract We examine the effect of labor mobility on venture capital (VC) investment. Following the staggered adoption of the inevitable disclosure doctrine that restricts labor mobility, VCs are less likely to invest in affected states. This effect is more pronounced when human capital is more important to startups, when VC investment is more uncertain, and when VCs’ monitoring costs are higher. The reduced innovation productivity of employees is a plausible underlying mechanism. To mitigate this adverse effect, VCs stage finance startups more and syndicate more with other VCs. Our paper sheds new light on the real effects of labor market frictions.